Direito ao esquecimento enquanto instrumento de efetivação dos direitos dos transgêneros - Galdino, Valéria Silva Galdino; Ruffo, Luiz Augusto; Cazelatto, Caio Eduardo Costa (Revista do Programa de Pós-Graduação em Direito, 2018)
The research analyzed, through bibliographic review, the realization of the right to be let alone in transgender individuals. In order to do so, we discussed the sources, the literary history of the subject in Brazil and the grounds for the application of the right to be let alone in the legal order of the country, as well as the negative aspects that its trivialization can cause in a hyper informational society. It was also examined the constitutional tension that unfolds from such right, as a paradox between freedom of information and human dignity, so that the vulgarization brought about by free information does not overlap on the legal protection of personality and life history of this sexual minority. In the same way, we investigated the main bills on the subject. By doing so it proposes, therefore, the extension of the right to be let alone for transgender individuals, especially so that they may have the autonomy in their lives assured in the face of their social vulnerability.